Inference of Short-Term Maximum Crack Width of RC Flexural Members Based on Interval Estimation Method. Issue 3 (March 2020) - Yao, Jitao; Yan, Hanbing; Yan, Mingdong
Abstract: The design method based on observation and experimental model only considers the design of ultimate limit state in related research, the application range is not wide. This paper takes the short-term maximum crack width of RC flexural members as an example, puts forward the application of this method in the design of serviceability limit state. Dimensionless method was used to collect 4665 pieces of RC flexural member crack width data, and the normality test was performed to obtain the type of probability distribution obeyed by the crack width. Considering the situation without parameter information and known coefficient of variation, a direct estimation formula for short-term maximum crack width of RC flexural members based on interval estimation method is proposed.